2019
DOI: 10.1177/1468087419864203
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study of the effect of nozzle diameter on diesel combustion ignition and flame stabilization

Abstract: The role of nozzle diameter on diesel combustion is studied by performing computational fluid dynamics calculations of Spray A and Spray D from the Engine Combustion Network. These are well-characterized single-hole sprays in a quiescent environment chamber with thermodynamic conditions representative of modern diesel engines. First, the inert spray evolution is described with the inclusion of the concept of mixing trajectories and local residence time into the analysis. Such concepts enable the quantification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 44 publications
3
19
0
Order By: Relevance
“…Their results were consistent with experimental observation, which showed no significant effect on IDT across the three D noz at T am of 1000K. Comparison of Spray D and Spray A was carried out in the numerical study by Desantes et al [13]. It was shown that a reduction in D noz promotes faster mixing which shortens the time needed to reach ignitable equivalence ratio, therefore shorter IDT.…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…Their results were consistent with experimental observation, which showed no significant effect on IDT across the three D noz at T am of 1000K. Comparison of Spray D and Spray A was carried out in the numerical study by Desantes et al [13]. It was shown that a reduction in D noz promotes faster mixing which shortens the time needed to reach ignitable equivalence ratio, therefore shorter IDT.…”
Section: Introductionsupporting
confidence: 82%
“…The equivalent diameter is calculated as d eq = D noz ρ f /ρ am , where ρ f denotes the density of fuel. It is also shown in [11,13] that the Z profiles for Spray A and Spray D collapse onto one another in normalized coordinates. It is hence possible to compare the Z fields for Spray A and Spray D against the experimental data for Spray A.…”
Section: Inert Spraymentioning
confidence: 89%
See 1 more Smart Citation
“…It generates a grid automatically during runtime at every time step. 34,35 To refine the mesh size, fixed embedding and adaptive mesh refinement (AMR) are used. Fixed embedding refines the grid at specific locations in the computational domain, such as at the location of injectors, spark plug, and intake valve seat, where finer resolution is needed to capture accurate in-cylinder conditions.…”
Section: Cfd Analysismentioning
confidence: 99%
“…Going into details of what is included in this special issue, we have 16 new papers 2337 covering all aspects of engine combustion network activities. There are 10 papers related to compression ignition engines 2332 while there are 6 papers related to gasoline direct injection, 3337 indicating that the research community is still trying to improve diesel engines even though the bad reputation they are facing lately. Dividing the papers into experimental or CFD work, we have 5 papers 2325,33,34 that deal with advance experimental diagnostics while 13 papers deal with CFD, 2632,3537 this is also a trend in the research community moving more and more into modeling work.…”
mentioning
confidence: 99%